Pemikiran Ki Hajar Dewantara terhadap Pendidikan - Suparlan Suparlan (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2018)
Raden Mas Soewardi Soerjaningrat was his real name but in 1922 became KI Hajar Dewantara, He was born in Yogyakarta on Thursday legi on 2 May 1889 as the 4th son of Prince Suryaningrat, the eldest son of the natures III. Childhood and adolescence is influenced by Javanese literature. Islam and the teachings of ancient Hinduism. The hero he admires from the epic mahabharata is yudistira (the symbol of peace and love) and Sri Krishna (the incarnation of wishnu filled with wisdom).Education is basically a conscious effort to cultivate the potential of human resources of learners by encouraging and facilitating their learning activities, as stated in the law. Facilitate learning activities such as learning aids such as school laboratories, books, classrooms, and others related to the needs of students and teachers in the learning process.